FORMULASI DAN EVALUASI EMULGEL SEBAGAI ALTERNATIF PENYEMBUHAN LUKA DENGAN KOMBINASI MAGGOT BSF (Hermetia Illucens) DAN BATANG BROTOWALI (Tinospora crispa Linn): Formulation And Evaluation Of Emulgel As An Alternative For Wound Healing With A Combination Of Maggot BSF (Hermetia Illucens) And Brotowali Stem (Tinospora crispa Linn - Wiwi, Neng Wiwi Whidiningsih; Suci, Suci Meyditia Oktafitri; Seni, Seni Fitriani Safitri; Siti, Siti Nisrina; Wina, Wina Yulianti (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2025)
BSF maggots contain protein ranging from 40-50%, which plays a crucial role in formation of new tissue in wounds, and fat content of 29-32%, which aids in collagen and epithelial tissue regeneration. The stem of brotowali acts as an antibacterial agent due to its flavonoid compounds, which form complexes with proteins and damage bacterial cell membranes. This study aims to determine the formulation and evaluation of the best emulgel preparation combining BSF maggots (Hermetia illucens) and brotowali stems (Tinospora crispa linn) as an alternative wound healing treatment. The formulations developed include F1, F2, F3, F4, and F5. F5 was identified as the best formulation, and evaluations were conducted through organoleptic tests, pH measurements, homogeneity, viscosity, adhesion, and antibacterial activity against Staphylococcus aureus. The results showed that the emulgel is white in color, has a distinctive odor, good consistency, pH suitable for skin, good homogeneity, good viscosity, adequate adhesion, and strong antibacterial activity against Staphylococcus aureus with an inhibition zone of 14 mm.